FLUCTUATIONS OF THE NONUNIFORM CYLINDRICAL ENVELOPE SUPPORTED WITH CROSS EDGES FROM MOVING LIQUID - Latifov, F. S.; Agayev, R. N. (Computer Science and Applied Mathematics, 2016)
In the offered article the free fluctuation supported with cross systems of edges, the nonuniform on thickness of the cylindrical envelope contacting from moving liquid is investigated. Using the variation principle of Hamilton-Ostrogradsky are constructed the set of equations of driving supported with cross systems of edges, the nonuniform on thickness of the cylindrical envelope contacting from moving